Formulation and Evaluation of Antidiabetic Polyherbal Tablets - Shinde, Sushilkumar A. (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: The goal of this study is to create and test antidiabetic polyherbal tablets made from several extracts of the chosen plant. Plants are usually a good source of medication. In reality, many currently accessible medications were produced from plants, either directly or indirectly. The anti-diabetic activity of a solid pharmaceutical dosage formulation containing a unique dry plant extract and several excipients such as starch, microcrystalline cellulose, and talc was reported to be statistically significant. Materials and Methods: The evaluation of prepared tablets is also discussed in this letter (weight variation, friability, hardness, and disintegration time). Results and Discussion: All of the values were within acceptable limits, according to the results of the preformulation experiments. The formulation has a fair amount of hardness (3.250.57), which aids in its rapid disintegration. The formulation’s friability (0.290.03) revealed that the tablets were mechanically stable. Because the average weight of the tablets was 340 mg, a weight variation of 7% is permissible. Conclusion: As a result, the weight variation test was passed on the full formed tablet. The mixtures took more than a minute to disintegrate finally, it may be concluded that the formed tablet requires additional research to properly understand the underlying mechanism of action, as well as long-term toxicity tests.